Buprenorphine Naloxone and Extended Release Injectable Naltrexone for the Treatment of Opioid Use Disorder Among a Veteran Patient Sample: A Retrospective Chart Review. Issue 3 (3rd July 2021) - Shirk, Steven D.; Ameral, Victoria; Kraus, Shane W.; Houchins, Joseph; Kelly, Megan; Pugh, Kendra; Reilly, Erin; Desai, Nitigna
Abstract: Objective: Previous research has demonstrated the effectiveness of both extended-release injectable naltrexone (XR-NTX) and buprenorphine/naloxone (BUP-NX) in the treatment of opioid use disorder (OUD). However, studies using real-world samples with multiple medical and psychiatric comorbidities are lacking. The study's primary aims were to: (1) compare clinical presentations in an inclusive sample of OUD-diagnosed US military veterans receiving XR-NTX and BUP-NX, and (2) investigate differences in 90-day treatment outcomes between these two groups. Methods: The medical records of 79 patients receiving medications to treat OUD in a VA hospital's addiction outpatient treatment program were reviewed retrospectively. The analysis included all veterans who initiated medication treatment during the study period. Differences between medication groups on co-occurring diagnoses, treatment retention, and related outcomes were examined. Results: The two groups were similar in medical and psychiatric comorbidity, although the BUP-NX group were more likely to have a pain diagnosis. No statistically significant differences in retention or toxicology results were found between the two groups over the 90-day study period. The rate of positive urine screens for the BUP-NX group was 19.2% for opiates and 13.5% for other illicit substances, and 3.7% and 11.1% respectively for the XR- NTX group. Conclusion: There was no evidence that 90-days outcomes differed for veterans based on medication received, and there were more similarities than differences in clinical characteristics. Additional research is needed, including larger sample size and prospective randomized control trial to evaluate VA patients' treatment outcomes receiving BUP-NX or XR-NTX for OUD.